René Daniëls : the words are not in their proper place - Daniëls, René; Groenenboom, Roland; van Adrichem, Jan; Museo Nacional Centro de Arte Reina Sofía; Stedelijk Van Abbemuseum (Rotterdam : NAi ; New York, NY : Distributed by Artbook/D.A.P. Inc., 2011)
This publication provides a unique retrospective of the multifaceted nature of the work of painter René Daniëls, against the backdrop of the art scene and underground culture of the 1970s and 1980s. Daniëls (b. 1950) is considered one of the leading Dutch painters of his generation. He gave the art of painting in the Netherlands a new élan like no one before him. In his work he links the visual arts and their rich past with history and everyday life. Ambiguity and double meanings play a major role in his work. A cerebral hemorrhage in 1987 made it impossible for Daniëls to work for an extended period, but his oeuvre is still relevant, vital, intelligent and a source of inspiration to new generations.
Text in English, translated from Dutch.
Catalog of the exhibition 'René Daniëls: An exhibition is Always Part of a Greater Whole,' held at the Museo Nacional Centro de Arte Reina Sofía, Madrid, Oct. 20, 2011- Mar. 26, 2012, and the Van Abbemuseum, Eindhoven, May 12-Sept. 23, 2012.
Translation of: René Daniëls : De woorden staan niet op hun juiste plaats
boek
Keywords: Daniëls, René